SEGREGATION ANALYSIS OF MORPHOLOGICAL CHARACTER AND BIOACTIVE GENOTYPE OF RICE PLANT F3 (CEMPO SALAMET/IR64) POPULATION - Ubaidillah, Mohammad (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2022)
Red rice contains high anthocyanin and bioactive antioxidant compounds that prevent free radical reactions. Cempo Salamet has potential as an antioxidant source, and the characteristics are red colored grains, 4–5 months old, 169 cm plant height, 7 productive tillers per plant, and resistance to blast disease. IR64 had been developed with the following characteristics: 3 months old, 85 cm plant height, 20–35 productive tillers per plant, resistance to brown leafhoppers pigment. This study aimed to obtain information on the segregation of the F3 population from crosses between the Cempo Salamet and IR64 varieties. Research methods included preparation and maintenance with genotype analysis. PCR analysis was conducted using SSR markers with primer RM346, RM316, RM228, and RM339. The segregation in F3 plants was 50% for >130 cm plant height, 51% for 10–19 tillers per plant, 67% for 2.2 g/100-grain weight, and 33% strong red for colour intensity. The findings demonstrated that SSR markers RM346, RM339, and RM228 could validate Cempo Salamet, IR64, and F3 DNA bands. However, RM316 could not validate all DNA bands in the research sample.